G1 scattered data interpolation with minimized sum of squares of principal curvatures - Azizan, Saaban; Abd R Mt Piah; Ahmad, Abdul Majid; Chang Hooi Tuang, Lawrence (Institute of Electrical and Electronics Engineering (IEEE), 2009)
Link to publisher's homepage at http://ieeexplore.ieee.org